2021
DOI: 10.1111/psyp.13950
|View full text |Cite
|
Sign up to set email alerts
|

Detecting a viewer’s familiarity with a face: Evidence from event‐related brain potentials and classifier analyses

Abstract: Human observers are highly efficient at recognizing the faces of the people they know (e.g., Bruce & Young, 2012) and accomplish this task many times every day without apparent effort. Yet the complexity of the task becomes evident when comparing familiar to unfamiliar face recognition (Young & Burton, 2018). It is usually easy to see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…Both time-resolved cross-classification and searchlight analyses yielded above-chance familiarity effects when trained on data from the Personal Familiarization experiment and tested on the matching task of the Perceptual Familiarization experiment. This suggests that seeing a familiarized face automatically and reliably elicits a familiarity response (Wiese et al 2022). The earliest indication of above-chance classification was at 170 ms and was most pronounced over central-posterior sites.…”
Section: Discussionmentioning
confidence: 99%
“…Both time-resolved cross-classification and searchlight analyses yielded above-chance familiarity effects when trained on data from the Personal Familiarization experiment and tested on the matching task of the Perceptual Familiarization experiment. This suggests that seeing a familiarized face automatically and reliably elicits a familiarity response (Wiese et al 2022). The earliest indication of above-chance classification was at 170 ms and was most pronounced over central-posterior sites.…”
Section: Discussionmentioning
confidence: 99%
“…M/EEG studies (Dobs, Isik, Pantazis, & Kanwisher, 2019; Karimi-Rouzbahani, Ramezani, Woolgar, Rich, & Ghodrati, 2021; Wiese, Tüttenberg, et al, 2019) in the past years reported on an electrophysiological correlate of face-familiarity between 200 to 600 ms following stimulus presentation. In a recent analysis Dalski et al (Dalski, Kovács, & Ambrus, 2022a) used data from three experiments reported in a study by Ambrus et al (2021) to investigate whether these familiarity signals generalize across participants, stimuli, and modes of familiarization.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent EEG investigation, Wiese et al (2022, Concealed Knowledge experiment) asked participants to acknowledge familiarity with a personally familiar identity, deny knowing another personally known identity, and give a truthful answer for a genuinely unfamiliar identity. This study mainly focused on two ERP components: the earlier N250 familiarity effect (Schweinberger & Neumann, 2016; Schweinberger, Pickering, Jentzsch, Burton, & Kaufmann, 2002), thought to reflect visual recognition of a known face, and the later sustained familiarity effect (SFE), hypothesized to be the marker of the integration of visual with additional identity-specific information (Wiese, Tüttenberg, et al, 2019). This study found that these components are present for both acknowledged and concealed stimuli; more specifically, measured over the TP9-TP10 and P9-P10 electrodes, they were found to be largely automatic in the ca.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations